A Participatory Systems Mapping (PSM) based approach towards analysis of business sustainability of rural Indian milk dairies - Vasanth Kamath; Seena Biju; Giridhar B. Kamath (Cogent Economics & Finance, 2019)
Drawing from the theories of Participatory Systems Mapping (PSM) this study presents an approach to analysing the business sustainability of entrepreneurial dairy ventures in India. The article begins with a general introduction to the small and medium scale dairy ventures in rural India, highlighting the prominent issues and challenges faced by the stakeholders. The second part demonstrates the use of the PSM framework in developing the Stock and flow diagram (SFD). Further, data from a local milk dairy is collected, and simulations are carried out between 2017-2025 using Vensim®. The outputs are analysed, and inferences are made. This study is expected to enable the policy makers towards the development of sustainable strategies for dairy businesses in general and enable the entrepreneur to analyse the future trends of the potential strategies under his consideration.
Keywords: 330; Participatory Systems Mapping; entrepreneurship; milk dairy; system dynamics; simulations